Implementation Of Community Based Tourism Principles In The Development Of Conservation Educational Tourism In Labuhan Ratu VII Village - Mukhlisatun Ifah Afiari; Rahayu Sulistiowati (The Eastasouth Journal of Social Science and Humanities, 2026)
This research is motivated by the potential of Labuhan Ratu VII Village, East Lampung Regency, as a buffer village for Way Kambas National Park, which has great potential for developing conservation education tourism. Although the community has been involved in tourism management, management practices still face various obstacles, such as suboptimal promotion, limited infrastructure, low community participation outside the core group, and irregular recording of tourist visit data. This study aims to describe and analyze the implementation of Community Based Tourism (CBT) in managing conservation education tourism in Labuhan Ratu VII Village. This study uses a qualitative method with a case study design, and a theoretical approach to the main development aspects of CBT according to Suansri (2003), which include economic, social, cultural, environmental, and political principles. The results show that the implementation of CBT has contributed to community development through job creation, increased community income, strengthening social and institutional roles, preserving local culture, and efforts to control tourism activities and conservation education. However, the resulting benefits have not been felt evenly and still require strengthening in aspects of community participation, promotion, and the role of local institutions.